Saint Sava Law (Nomocanon of Saint Sava) and Law of Stefan Dušan (Dušan’s Code): Sources of Law in Medieval Serbia - Miletić Branko А. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The paper deals with the sources of medieval Serbian law: Saint Sava Law (Nomocanon) from 1219 and Stefan Dušan’s Code from 1349 and 1354. Little is known about the Nomocanon of Saint Sava although it was a legal act used 130 years before the first part of Dušan’s Code. This legal source is rarely mentioned in the textbooks, hence the correctly applied phrase in theory is: “such a relation to Saint Sava Law is a manifestation of conscious denial and a lack of culture.“ Some authors add that this means “forgetting the rich legislative activity of one of the most important personalities of medieval Serbia.” Dušan’s Code, the Law of the Emperor Stefan Dušan, is the most important law (constitution) of medieval Serbia, which was made on the foundations of the Nomocanon. In some articles, Dušan’s Code directly refers to the Nomocanon (Articles 6, 8, 11, 01, 109, and 196). The author of this article points to these two very important works of Serbian medieval law and advocates for the return to the roots, the reaffirmation and the comprehensive study of the Saint Sava Law. This almost forgotten rule of civil law in medieval Serbia was the foundation of Dušan’s Code, from 1349 and 1354.